(untitled) (New York, N.Y., 2008)
The new Sixth Edition is the Molecular Cell Biology for a new generation, a dramatic revision of the classic text featuring two new co-authors, expanded coverage of immunology and development, and new media tools for students and instructors.
Di truyền phân tử nâng cao
Keywords: Molecular biology,Sinh học phân tử